A Review on Culture Diversity in Companies to Improve Competitiveness - Putri, Agustina Dian (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Purpose: The purpose of this study is to bring together the disparate literature on culture diversity, as well as to shed light on future research avenues in the field of culture diversity management. Design/Methodology: This research looked at a variety of empirical and conceptual studies on culture diversity and its implications. Using the literature published between 2000 and 2022. The paper uses secondary data gathered for the review of culture diversity. Findings: The literature evaluation was assigned to focus on cultural diversity in the workplace. Through this review, it is clear to understand the implications of cultural diversity in the modern era. According to the findings of the review, there are many studies in diversity and their results from the past few years. Further studies are needed both to add future sources of literature on diversity, especially cultural diversity in the workplace. Research limitations/implications: Because the main aim is to make only a detailed literary review and bring up different views about culture diversity, there are no theoretical interpretations nor personal critiques about the writers’ different perspectives in the paper. Practical Implication: This study examines the effectiveness of literature review in expanding existing knowledge in a particular area and formulating research prospects for future studies for researchers. Originality/Value: This study contributes theoretical perspectives as the key to managing diversity and developing diverse organizations.